The Use of Handicraft Art as a Visualization Method to Identify and Understand Chinese Tea Plants - Fatmawati Fatmawati; Fransiska Sella Pratiwi (Longda Xiaokan: Journal of Mandarin Learning and Teaching, 2023)
Tea plays a vital role in Chinese culture, impacting all ages and social groups. Its enduring presence across history highlights its significance within Chinese culture. Chinese Language and Culture learners should recognize tea's fundamental role, encompassing types, benefits, and origins. Handicraft art provides a creative approach, visually portraying unique tea characteristics for a deeper understanding. This research assesses handicraft art's effectiveness in recognizing and categorizing Chinese tea plant forms for Chinese language learners at the University Level. This pedagogical tool offers self-expression and creativity, fostering holistic learning experiences. The research engages 55 students to gather insights into the effectiveness of the handicraft art approach. Handicraft art enables exploration from botanical and artistic angles, highlighting its versatile teaching approach. Effective integrating instructional media with content motivates learner engagement and optimizes learning outcomes. This research employs handicraft art to enrich comprehension of Chinese tea culture's plant forms. Through creative expression and visual engagement, learners comprehensively understand the intricate world of Chinese tea culture.